Steel: Proof-oriented Programming in a Dependently Typed Concurrent Separation Logic - Fromherz, Aymeric; Rastogi, Aseem; Swamy, Nikhil; Gibson, Sydney; Martínez, Guido; Merigoux, Denis; Ramananandro, Tahina (26th ACM SIGPLAN International Conference on Functional Programming (ICFP 2021), 2021)
Steel is a language for developing and proving concurrent programs embedded in F*, a dependently typed programming language and proof assistant. Based on SteelCore, a concurrent separation logic (CSL) formalized in F*, our work focuses on exposing the proof rules of the logic in a form that enables programs and proofs to be effectively co-developed. Our main contributions include a new formulation of a Hoare logic of quintuples involving both separation logic and first-order logic, enabling efficient verification condition (VC) generation and proof discharge using a combination of tactics and SMT solving. We relate the VCs produced by our quintuple system to solving a system of associativity-commutativity (AC) unification constraints and develop tactics to (partially) solve these constraints using AC-matching modulo SMT-dischargeable equations. Our system is fully mechanized and implemented in F*. We evaluate it by developing several verified programs and libraries, including various sequential and concurrent linked data structures, proof libraries, and a library for 2-party session types. Our experience leads us to conclude that our system enables a mixture of automated and interactive proof, making it productive to build programs foundationally verified against a highly expressive, state-of-the-art CSL.